Acute Responses of Cardiac Biomarkers to Intermittent and Continuous Exercise Are Related to Age Difference but Not I/D Polymorphism in the ACE Gene - Falahati, Akram; Arazi, Hamid; Suzuki, Katsuhiko (Frontiers in Physiology, 2020)
Purpose: The purpose of this study was to determine (I) cardiac biomarkers (cTnI and NT-proBNP) responses to moderate-intensity continuous exercise (MICE) and high-intensity interval exercise (HIIE) in the middle-aged and young groups, (II) relationship of post-exercise cardiac biomarkers release between these two age groups, and (III) investigate whether I/D polymorphism in the ACE gene is associated with predisposition to cardiac damage after exercise in Iranian men. Methods: We examined cTnI and NT-proBNP in 29 middle-aged (54.5 ± 4.6 yr) and 28 young (22.7 ± 4.2 yr) soccer players before and after HIIE and MICE running tests. Resultsː The middle aged soccer players had higher baseline cTnI (0.015±0.007 ng/mL vs 0.010±0.006 ng/mL; P=0.01) and NT-proBNP (30.7±13.6 ng/L vs 18.4±8.3 ng/L; p<0.001) values compared with the young group. The changes with exercise (ΔcTnI: 13 vs 11 ng/mL and ΔNT-proBNP: 18 vs 11 ng/L) were also higher in the middle-aged group. No subject exceeded the upper reference limit (URL) for cTnI and NT-proBNP. Considering three ACE genotypes, the mean cTnI and NT-proBNP values of middle-aged and young groups did not show any significant difference. Conclusion: Marked differences in baseline and post-exercise cTnI and NT-proBNP values were observed which was related to age difference but not ACE genotypes.